The cruise tourism industry in the Canadian Arctic : analysis of activities and perceptions of cruise ship operators - Lasserre, Frédéric; Têtu, Pierre-Louis (Polar Record, 2016)
With the melting of sea ice in the Arctic, the potential for higher shipping access has markedly changed. Shipping activity in the Arctic is increasing, including tourism and exploration activities, underlining the need for reliable communication and monitoring. This article examines the interactions between climate and sea ice change, the patterns of cruise ship tourism through Arctic Canada and the interest of operators to increase their activities in the cruise tourism market in the region. Since 1995, the melting of the summer pack ice in the offers the possibilities of increased shipping in this region while encouraging speculation regarding the potential of the northwest passage (NWP) and the Canadian Arctic to become a major cruise maritime highway. Integrating research from both human and transport geography, this article presents an analysis of vessel movements. It also analyses perceptions of charters and cruise ship operators and of their interests in the cruise tourism market. Discussion is focused on issues associated with the lack of available vessels and maritime infrastructure, regulations in the Canadian arctic waters, security and search and rescue. This research could prove useful for communities, and policy makers, as well as the cruise sector itself, with regard to response to change in these remote locations.